INTERPRETING CHAUCER VIA BIBLICAL AND LITURGICAL TRADITIONS: CASE OF TRANSLATING «PRIORESS’S PROLOGUE» FROM «THE CANTERBURY TALES» IN TO MODERN ENGLISH AND UKRAINIAN - Shmiher, T. V. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2022)
Comparing the ways of receiving Chaucer’s text by today’s English and Ukrainian readers by assessing the possibilities of rendering the poetic techniques applied in Prioress’s Prologue, the author of the paper presents translation gains, losses and challenges which translators face when they have to decode and present an author’s historical and cultural experience encoded in the text. The paper deploys the original texts of Prioress’s Prologue as well as its translations into New English (1795-2007) and Ukrainian (2019). The intertextual richness of the Chaucerean text and literary culture is viewed from the points of biblical intertextuality, liturgical hymnography and religious poetry. Chaucer’s collage technique hides great power of ideological and aesthetical contrast, and the change of historical and cultural experience destruct the expected emotional impact in today’s audiences. The statuses of the biblical and liturgical prototexts contain different value for contemporary readers in intracultural and intercultural dimensions. In the theoretical perspective, all the ‘modernizations’ of Chaucer’s text are fully-fledged translations and require appropriate in-depth translation solutions.